ANALYSIS OF BOTNET CLASSIFICATION AND DETECTION BASED ON C&C CHANNEL - G C, Anup (My University, 2018)
Botnet is a serious threat to cyber-security. Botnet is a robot that can enter the computer and perform DDoS attacks through attacker’s command. Botnets are designed to extract confidential information from network channels such as LAN, Peer or Internet. They perform on hacker's intention through Command & Control(C&C) where attacker can control the whole network and can clinch illegal activities such as identity theft, unauthorized logins and money transactions. Thus, for security reason, it is very important to understand botnet behavior and go through its countermeasures. This thesis draws together the main ideas of network anomaly, botnet behavior, taxonomy of botnet, famous botnet attacks and detections processes. Based on network protocols, botnets are mainly 3 types: IRC, HTTP, and P2P botnet. All 3 botnet's behavior, vulnerability, and detection processes with examples are explained individually in upcoming chapters. Meanwhile saying shortly, IRC Botnet refers to early botnets targeting chat and messaging applications, HTTP Botnet targets internet browsing/domains and P2P Botnet targets peer network i.e. decentralized servers. Each Botnet's design, target, infecting and spreading mechanism can be different from each other. For an instance, IRC Botnet is targeted for small environment attacks where HTTP and P2P are for huge network traffic. Furthermore, detection techniques and algorithms filtration processes are also different among each of them. Based on these individual botnet's behavior, many research papers have analyzed numerous botnet detection techniques such as graph-based structure, clustering algorithm and so on. Thus, this thesis also analyzes popular detection mechanisms, C&C channels, Botnet working patterns, recorded datasets, results and false positive rates of bots prominently found in IRC, HTTP and P2P. Research area covers C&C channels, botnet behavior, domain browsing, IRC, algorithms, intrusion and detection, network and peer, security and test results. Research articles are conducted from scientific books through online source and University of Turku library.
Keywords: Botnet detection, Cyber Security, Algorithm, Clustering, Command and Control, IRC, HTTP, P2P